Iddah Belief Demands that are not Under The Husband's Capability in Palangka Raya City - Hidayati Taruna Huda; Abdul Helim; Muhammad Norhadi (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2024)
This research was motivated by a case that the researcher found in the wife’s application for idah maintenance, she did not ask for the amount of idah maintenance voluntarily but rather requested idah maintenance which burdened the husband. Therefore, this study focuses on why wives demand an income not by their husband’s abilities in Palangka Raya and how the husband’s attitude responds to the wife’s demands for an income that does not follow his abilities in Palangka Raya. The qualitative method used in this research uses empirical legal research with a sociological juridical type, with a socio- legal approach. The research results show: 1. The exwife demands a living that is not following the ex-husband’s capabilities in Palangka Raya,according to the theory of responsibility. The ex-husband has fulfilled his obligations. Benefits occur from providing idah maintenance according to the ex-husband’s capabilities as stipulated in the decision. 2. Ex-husbands in Palangka Raya respond to their wives’ demands regarding income with honesty and openness. The ex-husband showed a social attitude by promising to pay part of idah’s maintenance, although not in full. This attitude is important to maintain good relations and avoid bab prejudice in the future between husband and wife who have divorced.